Myth and historical facts about Rome and the Huns leader Attila - Imangazinov, M.M. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article ancient Greece myth and hystorical facts about Rome and the Huns leader Attila are considered. This article represents about the same pronunciation of the Italian and Kazakh word «Rome» and «Urym». In this article information of the European sources about the tribes and their leader Hun Attila, who influenced to the fall of the «Eternal City of Rome» is given. Attila is a hero of the Kazakh people, and he also was Edyl whose name has a huge and important place in the mythology and poetry of epic poems not only Kazakhs, but also the people of Europe. Moreover, his name appears in both stories, and in the mythology of various countries. He influenced to the story, tradition of variety countries. The question of the origin of Attila touches on the topic of the military campaign of the Huns with the Kipchak steppe to the west during the 4th century.
Ғұн басшысы Аттила жайлы мифтер жəне тарихи фактілер
Мифы и исторические факты о предводителе гуннов Аттиле
Keywords: Euripides; antiquity; Attila; huns; Rome; ancient legends